The role of the dynein light intermediate chain in retrograde IFT and flagellar function in Chlamydomonas - Reck, Jaimee (Mol Biol Cell, 2016)
The assembly of cilia and flagella depends on the activity of two microtubule motor complexes, kinesin-2 and dynein-2/1b, but the specific functions of the different subunits are poorly defined. Here we analyze Chlamydomonas strains expressing different amounts of the dynein 1b light intermediate chain (D1bLIC). Disruption of D1bLIC alters the stability of the dynein 1b complex and reduces both the frequency and velocity of retrograde intraflagellar transport (IFT), but it does not eliminate retrograde IFT. Flagellar assembly, motility, gliding, and mating are altered in a dose-dependent manner. iTRAQ-based proteomics identifies a small subset of proteins that are significantly reduced or elevated in d1blic flagella. Transformation with D1bLIC-GFP rescues the mutant phenotypes, and D1bLIC-GFP assembles into the dynein 1b complex at wild-type levels. D1bLIC-GFP is transported with anterograde IFT particles to the flagellar tip, dissociates into smaller particles, and begins processive retrograde IFT in <2 s. These studies demonstrate the role of D1bLIC in facilitating the recycling of IFT subunits and other proteins, identify new components potentially involved in the regulation of IFT, flagellar assembly, and flagellar signaling, and provide insight into the role of D1bLIC and retrograde IFT in other organisms.